A heterogeneous-agent model of growth and inequality for the UK - David Meenagh; Patrick Minford; Xiaoliang Yang (Cardiff University, Cardiff Business School, 2018)
This paper analyses the effect of wealth inequality on UK economic growth in recent decades with a heterogeneous-agent growth model where agents can enhance individual productivity growth by undertaking entrepreneurship. The model assumes wealthy people are more able to afford the costs of entrepreneurship. Wealth concentration therefore stimulates entrepreneurship among the rich and so aggregate growth, whose fruits in turn are largely captured by the rich. This process creates a mechanism by which inequality and growth are correlated. The model is estimated and tested by indirect inference and is not rejected. Policy-makers face a trade-off between redistribution and growth.
Keywords: E10; C63; O30; O40; 330; Heterogeneous-agent Model; Entrepreneurship; Aggregate Growth; Wealth Inequality; Redistribution; Indirect Inferencee